Reliability evaluation of a payment model in mobile e-commerce using colored Petri net - Pourali, Abdolghader; Malakooti, Mohammad V; Yektaie, Muhammad Hussein (Journal of Advanced Computer Science & Technology, 2014)
In general, a mobile payment system in mobile e-commerce must have high security so that the user can trust it for doing business deals, sales, paying financial transactions, etc. in the mobile payment system. Since an architecture or payment model in e-commerce only shows the way of interaction and collaboration among users and mortgagers and does not present any evaluation of effectiveness and confidence about financial transactions to stakeholders, in this paper we try to present a detailed assessment of the reliability of a mobile payment model in the mobile e-commerce using formal models and colored Petri nets. Finally, we demonstrate that the reliability of this system has high value (case study: a secure payment model in mobile commerce presented at the International Conference) [18]. Keywords: Reliability, Colored Petri Net, Assessment, Payment Models, M-Commerce.